Adult intensive care unit admissions with severe COVID-19 infection following emergency Caesarean section deliveries: A case series. (November 2021) - Morton, Sarah; Lamont, Holly; Silvey, Natalie; Browning, Thomas; Hayes, Michelle; Keays, Richard; Christie, Linsey; Davies, Roger; Singh, Suveer; Lockie, Chris; Sisson, Alice; Vizcaychipi, Marcela; et al.
Background: UK data suggest 6% of COVID-19 hospital admissions are either currently pregnant or immediately post-partum. However, the current literature suggests that if COVID-19 occurs in pregnancy, or post-partum, symptoms are mostly mild. Methods: All COVID-19 admissions to one acute London National Health Service Foundation trust were reviewed since the beginning of the COVID-19 pandemic to 1 May 2020 to establish whether there were any pregnant or immediately post-partum admissions. Data were extracted from hospital electronic records and anonymised. Any patients admitted to adult intensive care unit had their case notes reviewed in detail and comparison made to a local risk-assessment guideline identifying patients at-risk of thromboembolic events or cytokine storms. Local hospital guidelines were followed. Patients admitted to adult intensive care unit gave written consent. Results: A total of 24 pregnant or immediately post-partum patients with COVID-19 were admitted. Three patients required long adult intensive care unit admissions for severe single-organ respiratory failure after emergency C-sections. Two of these patients required proning (three times and eight times, respectively). All were considered medium risk for thromboembolic events but had rising D-dimers following adult intensive care unit admission, resulting in increased dosing of pharmacological thromboprophylaxis throughout their admission. All were considered low risk for a cytokine storm, and none had any significant cardiovascular or renal involvement. One patient developed a super-imposed fungal lung infection. All three patients developed delirium following cessation of sedation. Conclusion: Pregnant or immediately post-partum women can develop severe COVID-19 symptoms requiring prolonged adult intensive care unit admission. It is likely to be single-organ failure, but patients are at a high risk of a thromboembolic event and delirium.